Nonlinear integral inequalities with parameter and bounded solutions of dynamical systems - Ghrissi, Taouﬁk; Hammami, M. A. (Discontinuity, Nonlinearity, and Complexity, 2026)
We present in this paper some new nonlinear integral inequalities with parameter and we will use them to show the boundedness of solutions of perturbed nonlinear time-varying differential equations. Furthermore, some examples are given to illustrate the pplicability of the obtained results.